Efficient synthesis of functionalized olefins by wittig reaction using amberlite resin as a mild base - Valkute, Tushar R.; Aratikatla, Eswar K.; Bhattacharya, Asish K. (Synthetic Communications, 2017)
A convenient procedure for the synthesis of olefins by the reaction of stabilized, semistabilized, and nonstabilized phosphorous ylides with various aldehydes or ketone using Amberlite resin as a mild base is described. Our developed method offers facile and racemization-free synthesis of ,-unsaturated amino esters and chiral allylic amine. The developed methodology offers mild reaction conditions, high efficiency, and facile isolation of the final products, a practical alternative to known procedures